2020
DOI: 10.1371/journal.pone.0239600
|View full text |Cite
|
Sign up to set email alerts
|

Population-level assessment of atlas occipitalization in artificially modified crania from pre-Hispanic Peru

Abstract: Atlas occipitalization (AO) is a spinal anomaly, characterized by the fusion of the first cervical vertebra and occipital bone, with a complex etiology that can arise from congenital and environmental causes. AO has been reported in three regions of pre-Hispanic Peru in skeletal remains with artificial cranial modification (ACM), which involves the use of compression devices to permanently alter cranial shape and may have affected the fusion of the atlas and occipital bone. The aims of this study were to gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…AO is normally congenital, but in rare cases it may be a result of diseases such as osteomyelitis, arthritis, syphilis, tuberculosis and other infections or traumatic injuries of the cervical vertebrae [31,36]. Factors such as malnutrition or disease-related disturbances during development or genetic anomalies may also predispose a fetus toward developing AO [31].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…AO is normally congenital, but in rare cases it may be a result of diseases such as osteomyelitis, arthritis, syphilis, tuberculosis and other infections or traumatic injuries of the cervical vertebrae [31,36]. Factors such as malnutrition or disease-related disturbances during development or genetic anomalies may also predispose a fetus toward developing AO [31].…”
Section: Introductionmentioning
confidence: 99%
“…AO is normally congenital, but in rare cases it may be a result of diseases such as osteomyelitis, arthritis, syphilis, tuberculosis and other infections or traumatic injuries of the cervical vertebrae [31,36]. Factors such as malnutrition or disease-related disturbances during development or genetic anomalies may also predispose a fetus toward developing AO [31]. It has been reported that AO could be associated with Pfeiffer, Crouzon and Apert syndromes involving craniosynostosis, as well as with Goldenhar, Klippel-Feil and Pierre-Robin syndromes [5,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported prevalence of occipitalization ranges from 0.08% to 2.76%. [1][2][3][4] Clinically, occipitalization is one of the most common features of congenital atlantoaxial dislocations (AADs), which can cause severe neurological deficits and usually require surgical intervention. 5,6 These symptoms usually do not develop until the fourth or fifth decades of life.…”
mentioning
confidence: 99%
“…Occipitalization, or assimilation of the atlas, implies congenital bony union between the occiput and the first cervical vertebra (C1). The reported prevalence of occipitalization ranges from 0.08% to 2.76% 1–4. Clinically, occipitalization is one of the most common features of congenital atlantoaxial dislocations (AADs), which can cause severe neurological deficits and usually require surgical intervention 5,6.…”
mentioning
confidence: 99%